MANAGEMENT OF PSEUDOANEURYSM ON ARTERIOVENOUS FISTULA: SERIAL CASES FROM WEST JAVA - Prasetyo Edi; Radityo Utomo (JURNAL WIDYA MEDIKA, 2021)
Background: Pseudoaneurism is one of the many complications of dangerous AV shunt procedure. Their diagnosis and surgical treatment are important, because they can cause severe disability, including loss of upper extremity and hand. The usual techniques of pseudoaneurysm has 2 types, Ligation and patch with Fogarty thromboembolectomy. Objective: Here we reported 3 case of ruptured anastomotic and ruptured vein pseudoaneurysm of brachiocephalic arteriovenous fistula which has undergone surgical procedure. Methods: First case, a 29-years-old man presented with swelling and extreme pain in his right arm since 3 days ago. He had undergone AVF procedure 3 weeks ago. His right arm was accidentally squeezed by his mother 1 week after the surgery had been done. Second case, a 55-years-old patient presented with swelling, boils, and extreme pain in her left arm since 3 months ago. The patient's family said that the patient was often stabbed during multiple times of hemodialysis in the same place. Third case, a 65-year-old male patient, The patient fell from the motor 3 days ago, his right hand hit the motorcycle handlebar. The patient's AV fistula ruptured, was then taken to the hospital, the nurse dressing the wound, then planned for surgery. Results: Patient’s postoperative course went well and there was no sign of complication, such as ischemia. Arm swelling were reduced after 2 weeks follow up. Conclusion: The management of pseudoaneurysm can be done with different surgical methods depending on the cause and condition of the blood vessels. The management of pseudoaneurysm is not intended to save AVF but to save the patient from limb salvation and amputation.